2014
DOI: 10.1021/om501110w
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Thiol–Yne Click Chemistry of Redox-Active Ethynylferrocene

Abstract: The application of ethynylferrocene, FcCCH (1), as a highly efficient electroactive precursor for the thiol–yne click reaction is presented. For this purpose, a wide range of functionalized thiols, namely 2-mercaptoethanol, 1-thioglycerol, 3-mercaptopropionic acid, 4-aminothiophenol, and benzene-1,3-dithiol as well as tetrathiol pentaerythritol tetrakis(3-mercaptopropionate), were investigated. This facile thiol–ethynylferrocene radical reaction has resulted in the quantitative formation and isolation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 80 publications
2
23
0
3
Order By: Relevance
“…The one‐electron oxidation of ethynylferrocene, 1 , is known to be chemically reversible on the CV time scale . On a longer time scale, however, it had been previously reported that the lifetime of 1 + is much less than that generally observed for non‐H‐terminated ethynylferrocenes, and it was postulated that 1 + quickly dimerizes with loss of H‐atoms to form the butadiyne compound Fc−C 4 −Fc (Fc=ferrocenyl) .…”
Section: Resultsmentioning
confidence: 99%
“…The one‐electron oxidation of ethynylferrocene, 1 , is known to be chemically reversible on the CV time scale . On a longer time scale, however, it had been previously reported that the lifetime of 1 + is much less than that generally observed for non‐H‐terminated ethynylferrocenes, and it was postulated that 1 + quickly dimerizes with loss of H‐atoms to form the butadiyne compound Fc−C 4 −Fc (Fc=ferrocenyl) .…”
Section: Resultsmentioning
confidence: 99%
“…[99] Wicking,c ell transport, and interlocking capabilities can be Figure 11. [83] Angewandte Chemie Reviews imparted to the fibers depending on the shape of the fibers produced. Reproducedwith permission from The American Chemical Society.C opyright 2014.…”
Section: Fabrication Of Functional Materials Through Microfluidicsmentioning
confidence: 99%
“…[82] TheM anners group has investigated the preparation of organometallic compounds for many years,i ncluding recent forays into using thiol-coupling reactions to develop polyferrocenyl homopolymers with silane linkages. [83] This suggests that orthogonal reactions could perhaps be used for further coupling at these bonds.U ltimately the simplicity of the process to develop novel compounds that retain the properties of their precursors could conceivably be applied to various other organic and inorganic molecules with known electroactive and/or optical properties. In addition to presenting various ways to incorporate ferrocene,t hese reports also outline the electrochemical aspects of the materials produced.…”
Section: Organometallic Coupling Reactionsmentioning
confidence: 99%
“…Die Gruppe von Manners erforscht seit vielen Jahren intensiv auf dem Gebiet der Entwicklung metallorganischer Verbindungen, unter anderem durch die Anwendung von Thiol‐Kupplungen zum Aufbau von Polyferrocenyl‐Homopolymeren über Silanbindungen . Kürzlich nutzten auch Cuadrado und Mitarbeiter Thiol‐En‐ und Thiol‐In‐Reaktionen zum Einbau von Ferrocen als Gerüstmolekül, Seitenkettenmolekül oder peripheres Molekül in Polymerfilme mit und ohne verbindende Silangruppen (Abbildung ). Neben der Darstellung verschiedener Wege zum Ferroceneinbau behandeln diese Berichte auch elektrochemische Aspekte der hergestellten Materialien.…”
Section: Thiol‐kupplungenunclassified
“…Außerdem demonstrierten die Autoren, dass die zur Bildung dieser elektroaktiven Polymere genutzten Thiol‐Kupplungen ohne Anwendung von Wärme oder Photoinitiierung durchgeführt werden können. Im Gegensatz zu dem für Thiol‐In‐Reaktionen typischen zweistufigen Kupplungsprozess erfolgte bei der Verwendung von Ethinylferrocen als Ausgangskomponente keine zweifache Hydrothiolierung unter den untersuchten Bedingungen, was zu schwefelverbrückten Ferrocenylvinyl‐Einheiten führte . Das deutet darauf hin, dass möglicherweise eine weitere Kupplung an diesen Bindungen über orthogonale Reaktionen erfolgen könnte.…”
Section: Thiol‐kupplungenunclassified